Pertunjukan Partisipasi Pantun Palang Pintu di Kecamatan Mandau, Kabupaten Bengkalis, Riau - Freddy Antara; Mariana Heristian; Agusti Efi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Pantun Palang Pintu is a form of traditional art performance by the people of the sub-district. Mandau. Regency. Bengkalis which is usually used in welcoming the bride and groom and entertainment for its supporting community. The interaction in the performance of the pantun creation process is spontaneous. In this case the messages conveyed are socio-cultural realities as material for the interaction of participation in producing meaning and exchanging experiences related to people's lives. This study aims to determine the performance of palang Pintu rhyme in the people of Riau, especially in the people of the sub-district. Mandau, Regency. Bengkalis. This study uses a qualitative descriptive method and the analysis used is the data obtained, both written data and data obtained in the field through interviews and collected and described and then analyzed with the problems that have been formulated. cloth known as doorstop and the existence of reciprocal pantun activities. With the participation of the audience or extended family, both parties explained that the Pantun Palang Pintu performance was in Mandau District. Bengkalis Regency is a participation show.